A Study on The Relationship between Parental Involvement and Reading Performance of Grade VI Students in Pajo Elementary School - Yopo, Mea (Future Science / FSH-PH Publications, 2024)
This study looks into the relationship between parental involvement and reading performance of Grade VI students in Pajo Elementary School, Tarangan, Samar. Specifically, it aimed to identify the reading proficiency of students in Grade VI at Pajo Elementary School in general and grouped in terms of: a) frustration b) Instructional and c) Independent; determine how do parents view parental involvement practices in relation to their child's reading performance; and to know if there is a significant correlation between parents' involvement practices and their children's reading ability. Descriptive and quasi-experimental design were employed in the study. Numerical and non-numerical data were gathered from both the student-respondents and parents-respondents. Interview guide was employed for the focus group discussion with the parents.